Easy Living : The Rise of the Home Office - Patton, Elizabeth A (Rutgers University Press, 2020)
How did Americans come to believe that working at home is feasible, productive, and desirable? Easy Living examines how the idea of working within the home was constructed and disseminated in popular culture and mass media during the twentieth century. Through the analysis of national magazines and newspapers, television and film, and marketing and advertising materials from the housing, telecommunications, and office technology industries, Easy Living traces changing concepts about what it meant to work in the home. These ideas reflected larger social, political-economic, and technological trends of the times. Elizabeth A. Patton reveals that the notion of the home as a space that exists solely in the private sphere is a myth, as the social meaning of the home and its market value in relation to the public sphere are intricately linked.